1988
DOI: 10.1111/j.1471-0528.1988.tb06568.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone histology and mineral homeostasis in human pregnancy

Abstract: Summary. Mineral homeostasis was studied biochemically and histologically in patients in early pregnancy and at term. In early pregnancy there was evidence of increased and reversible resorption of bone, whereas in late pregnancy bone demonstrated active formation and rapid mineralization with minimal resorption. Gut absorption of calcium was not increased in early pregnancy. The overall findings were consistent with calcium liberation from bone in early pregnancy, and with enhanced conservation of bone calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 19 publications
4
43
1
1
Order By: Relevance
“…(12,13) The bone biopsy data of Purdie et al in women at the time of termination of pregnancy (12-14 weeks gestation) was a landmark study in its suggestion that bone resorption predominates in early pregnancy and we have been able to confirm and quantify noninvasively the level of this increase in bone resorption. (14) Our data indicate that there is a dissociation of bone formation and resorption in the first two trimesters and well into the third trimester of pregnancy. In a nonpregnant young adult woman bone turnover is in balance with bone resorption equaling bone formation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…(12,13) The bone biopsy data of Purdie et al in women at the time of termination of pregnancy (12-14 weeks gestation) was a landmark study in its suggestion that bone resorption predominates in early pregnancy and we have been able to confirm and quantify noninvasively the level of this increase in bone resorption. (14) Our data indicate that there is a dissociation of bone formation and resorption in the first two trimesters and well into the third trimester of pregnancy. In a nonpregnant young adult woman bone turnover is in balance with bone resorption equaling bone formation.…”
Section: Discussionmentioning
confidence: 88%
“…(11)(12)(13) Bone biopsy from early pregnancy (12-14 weeks) and late pregnancy (38-40 weeks) suggested that there may be a two-phase bone response to pregnancy with an early phase of bone resorption and a later bone formation phase. (14) Previous authors have studied women once pregnant and few studies have had prepregnancy data available. This has meant that full evaluation of bone turnover in pregnancy has not been possible.…”
Section: Introduction Omentioning
confidence: 99%
“…At the first trimester time point, bone resorption indexes were increased, bone formation indexes were decreased, and trabecular bone volume was significantly lower, compared with nonpregnant women (732). Conversely, the third-trimester biopsies were no different from the nonpregnant values for bone mass and indexes of bone resorption and formation (732). Taken at face value, these results suggest that early pregnancy is a bone-resorptive state, which induces bone loss that is later recovered by the end of pregnancy.…”
Section: Human Datamentioning
confidence: 99%
“…The sole study reporting iliac crest histomorphometry during human pregnancy was carried out in 15 women who planned to have elective first trimester abortions, 13 women scheduled to have C-sections in the third trimester, and 40 nonpregnant women (some living and some cadaveric specimens) (732). At the first trimester time point, bone resorption indexes were increased, bone formation indexes were decreased, and trabecular bone volume was significantly lower, compared with nonpregnant women (732).…”
Section: Human Datamentioning
confidence: 99%
“…Given the invasiveness of the procedure, there is limited information in the human, and unfortunately, none that is recent. In an apparent paradox with the increased transfer of calcium to the fetal compartment during the second half of pregnancy, one study detected a reduction in bone resorption and promotion of bone formation and mineralization in the maternal compartment during that period (58).…”
Section: Histologymentioning
confidence: 99%